1978
DOI: 10.1099/00221287-104-1-139
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomy of Phylloplane Bacteria Isolated from Lolium perenne

Abstract: I39Phenetic data on over 600 heterotrophic bacteria from green leaves of Lolium perenne s24 were collected and analysed using numerical taxonomic methods. Marker strains representing 60 taxa were included in the analyses. At similarity levels of 80 % or above, 74 % of the isolates were recovered in six major and 45 minor phena. Four of the major phena were equated with the taxa Listeria grayilmurrayi, PseudomonasJiTuorescens, Staphylococcus saprophyticuJ and Xanthomonas campestris; the two unidentified phena c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…In general, the micro-organisms isolated were similar to those from previous studies of Loliurn perenne (Dickinson et al, 1975;Austin et al, 1978) and other temperate plants (Last & Deighton, 1965;Preece & Dickinson, 1971;Dickinson & Preece, 1976).…”
Section: Discussionsupporting
confidence: 71%
“…In general, the micro-organisms isolated were similar to those from previous studies of Loliurn perenne (Dickinson et al, 1975;Austin et al, 1978) and other temperate plants (Last & Deighton, 1965;Preece & Dickinson, 1971;Dickinson & Preece, 1976).…”
Section: Discussionsupporting
confidence: 71%
“…Several ecological studies have shown that this group forms a significant part of bacterial communities of a number of plant species (Austin et al, 1978 ;Bell et al, 1995 ;Ercolani, 1991 ;Legard et al, 1994 ;McInroy & Kloepper, 1995 ;Thompson et al, 1993). Because of difficulties in taxonomic characterization on the basis of phenotypic features, most of the isolated strains have been identified at the genus level or affiliated to Curtobacterium flaccumfaciens and Clavibacter michiganensis without further specification at the subspecies or pathovar level.…”
Section: Introductionmentioning
confidence: 99%
“…The most important species are Pseudomonas syringae and Erwinia Herbicola (Hew and Yang, 1992) very common and widely distributed on plant epiphytes and leaves of trees (Maki et al, 1974;Arny et al, 1976;Kozloff et al, 1983;Ercolani, 1991). Much more frequently observed bacteria are Pseudomonas fluorescens and Xanthomonas campestris (Austin et al, 1978;Obata et al, 1987;Hew and Yang, 1992), normally being residents in soil and water, and even on leaves of trees, pepper and tomato (Austin et al, 1978;Maki and Willoughby, 1978;Warren et al, 1986). Much less frequent are E. ananas (Hew and Yang, 1992) and P. viridiflava (Obata et al, 1989), which are associated with tea plants and some other crops in Japan (Abe et al, 1989).…”
Section: Introductionmentioning
confidence: 99%